STANDARDIZATION OF VULNERABILITY MAPS - Neukum Ch.; Hötzl H. (My University, 2007)
Groundwater vulnerability assessment schemes are used for the estimation of potential groundwater contamination at different scales and on different administrative levels. However, the term vulnerability is not standardized and the available methods are not able to give a unique assessment of vulnerability creating thus uncertainty in the interpretation and in further application concerning decision creation processes. To judge the information of vulnerability maps certainly and to value the general trends of vulnerability assessment of different methods, four different vulnerability methods of the parametric system group have been applied on a karst area in southwestern Germany to perform a comparative assessment and correlation of these vulnerability assessment methods, namely DRASTIC, PI, EPIK, and GLA. It is shown that by means of simple statistical considerations the first highly different vulnerability maps could be made more coherent after reclassification. The reclassified vulnerability assessments show a more consistent vulnerability distribution pattern and provide the possibility of area-wide validation of the maps as the chosen vulnerability classification is theoretically connected to the mean transit time of percolation water and is largely independent of the applied vulnerability assessment method.
Keywords: VULNERABILITY; GROUNDWATER MANAGEMENT; KARST; GROUNDWATER PROTECTION; GERMANY